Outcome after surgical treatment of fragility ankle fractures in a certified orthogeriatric trauma center. Issue 8 (August 2018) - Schray, D.; Ehrnthaller, C.; Pfeufer, D.; Mehaffey, S.; Böcker, W.; Neuerburg, C.; Kammerlander, C.; Zeckey, C.
Abstract: Introduction: Orthogeriatric ankle fractures seem to play an essential role in terms of quality of life in the elderly. Knowledge of the outcome after orthogeriatric ankle fractures is sparse. The present study investigates the outcome after surgically treated ankle fractures at a certified orthogeriatric trauma center. Material & Methods: A retrospective observational study was performed investigating the outcome of surgically treated ankle fractures in orthogeriatric patients between 2015-2017. Outcome parameters included but were not limited to the EQ-5D 3 L, Barthel Index, Karlsson Score and the Charlson Comorbidity Index. Housing situation and mobility were evaluated and potential associations to the fracture pattern and the related treatment strategy were investigated. Results: In total, 58 patients were included (age 77.7 ± 6, 2 years). The majority were AO-44 B2 fractures (72%). General outcome was related to the Parker score; a Parker Score of 9 prior surgery was independently associated with an improved outcome according to the EQ-5D 3 L and Barthel Index. Patients under 80 years of age also had better results. Place of residence did not significantly change after surgery. Neither different types of implants nor initial use of an external fixator (e.g. open fractures) did influence outcome. A wound healing impairment was found in 10% of our patients whereas the overall unplanned reoperation rate was 7%. Overall complication rate was 20%, one-year mortality was 10%. Conclusions: Surgically treated ankle fractures in the elderly which are treated in a certified geriatric fracture center seem to have limited negative effect on their quality of life. We did not observe the otherwise often demonstrated high mortality rates, but still nearly half of the patients demonstrated perioperative complications, which emphasizes the need for optimal perioperative care at an orthogeriatric trauma center. Since there was a reasonable number of patients with wound healing issues this study supports the idea of a staged protocol using external fixation with secondary ORIF.